Chloride and CO2 transport in cement paste containing red mud. (September 2015) - Díaz, Belén; Freire, Lorena; Nóvoa, X. Ramón; Pérez, M. Consuelo
Abstract: Red mud, RM, is the main residue generated in the Bayer process for obtaining alumina. This paper gives an assessment on the penetration rate of aggressive substances such as chlorides and CO2 through RM incorporated cement paste. Diffusivity values are significantly reduced in presence of a low RM content, which could contribute to an increase in the service life of the reinforcements. A study based on Mercury Intrusion Porosimetry (MIP) and Differential Scanning Calorimetry (DSC) was performed to clarify the decrease in the penetration rates. This paper emphasizes the relevance of performing an exhaustive microstructural analysis to have a better understanding of the changes induced not only due to the RM incorporation but also those produced after the chloride and CO2 entrance. Regarding the chloride penetration, the high aluminium content of RM, able to trap chlorides to produce Friedel's salt, is pointed as responsible for the reduction in the chloride diffusivity. On the other hand, the retention in the CO2 penetration is assisted by the larger amount of C-S-H gel developed in the RM-mixtures along with the alkaline nature of the residue. A reasonable prediction of the carbonation progress can be obtained by measuring the weight increment as the experiment advances.